Applicability of bacterial biocementation in sustainable construction materials - Dhami, Navdeep; Mukherjee, Abhijit; Reddy, M. (John Wiley & Sons, Ltd, 2016)
Urease production of calcifying bacterium, Bacillus megaterium SS3 was enhanced by using response surface methodology (RSM) in current study. The preliminary screening by Plackett–Burman's design revealed that among the tested factors, glucose, urea and NaHCO3 significantly (p < 0.05) enhanced the urease production. Further optimization of urease production by B. megaterium through RSM was achieved as 879 U mL−1 in the presence of glucose (21.7 g L−1), urea (21.1 g L−1) and NaHCO3 (1.9 g L−1) compared to 640 U mL−1 in unoptimized medium. The effect of different factors seems to promote the growth of bacterial isolate leading to improvement in urease production. As production of carbonates by ureolytic bacteria is dependent on urease enzyme, improvement in enzyme production enhanced the carbonate precipitation efficacy to 1.7-fold in optimized medium. Carbonic anhydrase production also increased from 120 U mL−1 to 190 U mL−1 in optimized medium.